PENGARUH DIVIDEN PER SHARE DAN EARNING PER SHARE TERHADAP HARGA SAHAM INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA PADA PERIODE 2008 -2012 - Rudi Setiawan (Journal Of Regional Public Administration (JRPA), 2018)
This research is approved to know the effect of Dividend Per Share (DPS) and Earning Per Share (EPS) on stock prices at Go Public companies in the ExchangeIndonesia securities and based on samples (purposive sampling) in cankan 7 companies Manufacturing industries that report complete and published financial reports Dividend for five consecutive years ie from 2008 to 2012. DataUsed is secondary data. The results showed thatPartial DPS has no significant effect on the stock price of the company Manufacturing industry in Indonesia Stock Exchange 2008 period s.d. 2012. In terms of theory, The results of this study are in accordance with the first opinion in the irrelevance theory The influence of dividend policy on stock prices. This theory assumes that Dividend policy has no impact on the value of the company. While Partially EPS has a significant influence on the stock price of the company Manufacturing industry in Indonesia Stock Exchange 2008 period s.d.2012. EPS and DPS Simultaneous (together) have a significant effect on stock prices Manufacturing industry companies in Indonesia Stock Exchange.